New vessels formation in young strokes with isolated steno‐occlusive MCA. Issue 10 (15th September 2018) - Liang, Meng; Wang, Peng; Ma, Yan; Zhang, Xiaohao; Gao, Jie; Ma, Minmin; Dai, Zhengze; Liu, Dezhi; Liu, Xinfeng
Abstract: Objective: New vessels formation (NVF) along the steno‐occlusive middle cerebral artery (MCA) is often observed in digital subtraction angiography (DSA) imaging. In the study, we aim to explore the clinical relevance of NVF in young ischemic stroke patients with isolated middle cerebral artery (MCA) stenosis. Methods: We retrospectively reviewed the digital subtraction angiography (DSA) images of 93 young ischemic stroke patients (age ≤ 45 years old) in our center from January 2006 to June 2016. All the patients were diagnosed with isolated steno‐occlusive middle cerebral artery (MCA) disease.NVF was defined as new vessels formation along the stenotic MCA on anteroposterior DSA projection. The association between NVF and functional outcome was analyzed. Results: The prevalence of NVF was 0 in moderate stenosis, 15.8% in severe stenosis, and 53.7% in MCA occlusions. The presence of NVF had a strong correlation with the severity of MCA stenosis ( r  =   0.467, p  <   0.001). Compared to patients without NVF, patients with NVF were more likely to suffer an unfavorable functional outcome (6.2% vs. 21.4%, p  = 0.061) at 3 months. Univariate logistic regression analysis showed that NVF was associated with unfavorable outcome [Odds Ratio (OR) = 4.159, 95% confidence intervals (CI) = (1.072, 16.137), p  =   0.039]. Conclusions: This study demonstrated that NVF were associated with poor clinical outcome in young ischemic stroke patients who were diagnosed with isolated steno‐occlusive MCA. Abstract : New vessels formation was significantly correlated with the severity of MCA stenosis in young ischemic stroke patients with isolated MCA steno‐occlusive disease. In terms of stroke outcome, NVF predicts unfavorable outcome at 3 months after symptom onset.